Prognostic Value of Inflammatory Markers in Septic Critically Ill Patients with Chronic Liver Disease: A Retrospective Analysis*
Background/Aims: Septic patients with chronic liver disease (CLD) experience high morbidity and mortality rates, particularly in the intensive care unit (ICU) setting, due to immune dysfunction. Despite their vulnerability, data on prognostic markers remain scarce, particularly when assessed in conjunction with disease severity scores. This study aimed to evaluate the prognostic value of various inflammatory markers, including white blood cell count (WBC), neutrophil-to-lymphocyte ratio (NLR), lactate, and lactate-to-albumin ratio (LAR), in septic critically ill CLD patients. Materials and Methods: A retrospective cohort study was conducted on 126 septic CLD patients admitted to ICU. Data on demographics, clinical scores, inflammatory markers, and clinical outcomes were collected. Logistic regression and ROC analyses were used to identify independent predictors of ICU mortality. Results: Intensive care unit mortality was 66%. In addition to higher Acute Physiology and Chronic Health Evaluation II (APACHE II) (39.3 Å